Pycnometric-Additive Determining of the Degree of Coating of High-Strength Synthetic Diamond Grinding Powders using the Actual 3D Morphology of their Grains - Petasyuk, G.A.; Bochechka, O.O.; Lavrinenko, V.I.; Poltoratskyi, V.G.; Syrota, Yu.V.; Bilochenko, V.P. (Journal of Coating Science and Technology, 2023)
The methodological components of direct and indirect analytical determining of the degree of coating of synthetic diamond grinding powders are analyzed. It has been established that the weight method most used in practice for determining this technological property of grinding powder is not universal for different methods of applying the coating. More universal in this regard, as the review of publications showed, is the well-known indirect-analytical method based on the pycnometric-additive approach. An improved variant of this method is proposed, aimed at application to high-strength synthetic diamond grinding powders. The method takes into account the peculiarities of the 3D morphology of the grains of such powders. Using the example of grinding powder AC300 500/400, the grains of which were coated with a solution of a mixture of boron oxide, sodium silicate, and titanium carbide, the advantages of using the proposed method are illustrated. The results of a comparison of determining the degree of coating by a known method and its improved variant are presented.